Critical role of phosphodiesterase 2A in mouse congenital heart defects. Issue 6 (2nd February 2018) - Assenza, Maria Rita; Barbagallo, Federica; Barrios, Florencia; Cornacchione, Marisa; Campolo, Federica; Vivarelli, Elisabetta; Gianfrilli, Daniele; Auletta, Luigi; Soricelli, Andrea; Isidori, Andrea M; Lenzi, Andrea; Pellegrini, Manuela; et al.
Abstract: Aims: Phosphodiesterase 2 A (Pde2A), a cAMP-hydrolysing enzyme, is essential for mouse development; however, the cause of Pde2A knockout embryonic lethality is unknown. To understand whether Pde2A plays a role in cardiac development, hearts of Pde2A deficient embryos were analysed at different stage of development. Methods and results: At the stage of four chambers, Pde2A deficient hearts were enlarged compared to the hearts of Pde2A heterozygous and wild-type. Pde2A knockout embryos revealed cardiac defects such as absence of atrial trabeculation, interventricular septum (IVS) defects, hypertrabeculation and thinning of the myocardial wall and in rare cases they had overriding aorta and valves defects. E14.5 Pde2A knockouts showed reduced cardiomyocyte proliferation and increased apoptosis in the IVS and increased proliferation in the ventricular trabeculae. Analyses of E9.5 Pde2A knockout embryos revealed defects in cardiac progenitor and neural crest markers, increase of Islet1 positive and AP2 positive apoptotic cells. The expression of early cTnI and late Mef2c cardiomyocyte differentiation markers was strongly reduced in Pde2A knockout hearts. The master transcription factors of cardiac development, Tbx, were down-regulated in E14.5 Pde2A knockout hearts. Absence of Pde2A caused an increase of intracellular cAMP level, followed by an up-regulation of the inducible cAMP early repressor, Icer in fetal hearts. In vitro experiments on wild-type fetal cardiomyocytes showed that Tbx gene expression is down-regulated by cAMP inducers. Furthermore, Pde2A inhibition in vivo recapitulated the heart defects observed in Pde2A knockout embryos, affecting cardiac progenitor cells. Interestingly, the expression of Pde2A itself was dramatically affected by Pde2A inhibition, suggesting a potential autoregulatory loop. Conclusions: We demonstrated for the first time a direct relationship between Pde2A impairment and the onset of mouse congenital heart defects, highlighting a novel role for cAMP in cardiac development regulation.